HPLC-ESI-MS/MS assessment of the tetrahydro-metabolites of cortisol and cortisone in bovine urine: promising markers of dexamethasone and prednisolone treatment. Issue 7 (2nd July 2016) - Chiesa, Luca; Panseri, Sara; Pavlovic, Radmila; Cannizzo, Francesca Tiziana; Biolatti, Bartolomeo; Divari, Sara; Villa, Roberto; Arioli, Francesco
ABSTRACT: The effects of long-term administration of low doses of dexamethasone (DX) and prednisolone (PL) on the metabolism of endogenous corticosteroids were investigated in veal calves. In addition to cortisol (F) and cortisone (E), whose interconversion is regulated by 11β-hydroxysteroid dehydrogenases (11βHSDs), special attention was paid to tetrahydrocortisol (THF), allo-tetrahydrocortisol (aTHF), tetrahydrocortisone (THE) and allo-tetrahydrocortisone (aTHE), which are produced from F and E by catalytic activity of 5α and 5β-reductases. A specifically developed HPLC-ESI-MS/MS method achieved the complete chromatographic separation of two pairs of diastereoisomers (THF/aTHF and THE/aTHE), which, with appropriate mass fragmentation patterns, provided an unambiguous conformation. The method was linear ( r 2  > 0.9905; 0.5–25 ng ml −1 ), with LOQQ of 0.5 ng ml −1 . Recoveries were in range 75–114%, while matrix effects were minimal. The experimental study was carried out on three groups of male Friesian veal calves: group PL ( n  = 6, PL acetate 15 mg day –1 p.o. for 31 days); group DX ( n  = 5, 5 mg of estradiol (E2) i.m., weekly, and 0.4 mg day –1 of DX p.o. for 31 days) and a control group ( n  = 8). Urine was collected before, during (twice) and at the end of treatment. During PL administration, the tetrahydro-metabolite levels decreased gradually and remained low after the suspension of treatment. DX reduced urinary THF that persisted after the treatment, while THE levels decreased during the experiment, but rebounded substantially after the DX was withdrawn. Both DX and PL significantly interfered with the production of F and E, leading to their complete depletion. Taken together, the results demonstrate the influence of DX and PL administration on 11βHSD activity and their impact on dysfunction of the 5-reductase pathway. In conclusion, profiling tetrahydro-metabolites of F and E might serve as an alternative, indirect but reliable, non-invasive procedure for assessing the impact of synthetic glucocorticosteroids administration. GRAPHICAL ABSTRACT: